Ekoteologi Pro-Lingkungan di Desa Sugihen: Analisis Efektifitas Program Plag Jalan, Himbauan Sampah dan Budidaya Serai - Aida Mardiah; Siti Aisyah; Annisa Fadillah; Elvira Nurlita Sibarani; Siti Nurhaliza Br Lubis (Universitas 45 Surabaya, 2025)
The 2025 Community Service Program (KKN) of the State Islamic University of North Sumatra (UINSU), held in Sugihen Village, Juhar District, implemented an Ecotheology approach as a form of environmental awareness that combines Islamic values and ecological awareness in community life. This study aims to evaluate the effectiveness of three main programs: the installation of road signs, waste management appeals, and lemongrass planting implemented by KKN students as a tangible contribution to environmental sustainability. A qualitative approach with a case study method was used in data collection through observation, interviews, and documentation during the one-month program implementation. The findings indicate that all three programs have a positive impact on increasing community awareness and involvement in protecting the environment. Road signs play a role in clarifying regional planning and facilitating access to public facilities such as mosques, schools, and other places of worship. Meanwhile, the waste campaign has begun to change residents’ habits of littering, and lemongrass cultivation activities are used to beautify yards while having economic value and strengthening the value of mutual cooperation. In conclusion, the Ecotheology concept applied in this KKN activity has proven effective in encouraging positive changes in community behavior toward the environment and has the potential to serve as an example for implementation in other villages.